Efektivitas Role Playing Dalam Mendeskripsikan Mata Pelajaran Kimia Pada Materi Bentuk Molekul Untuk Meningkatkan Hasil Belajar Dan Kemampuan Bernalar Kritis Pesrta Didik Kelas X SMAN 3 Pamekasan - Ulfah, Laily; Huda, Nuril; Utami, Sri (Peneliti.net, 2024)
This study aims to examine the effectiveness of role playing in describing the chemistry subject of molecular form material to improve learning outcomes and critical reasoning skills, compared to conventional learning which is only done by lecture method. Most of the chemistry lessons are abstract in nature, requiring high imagination and critical reasoning skills. Likewise, the molecular form material has a complex structure with constituent atoms in various shapes and angles. To help students in this learning, the role playing method was chosen which can involve students directly, train them to work together, express ideas, solve problems, analyze, evaluate and conclude. This study uses a quantitative approach with a pretest and posttest design in the experimental and control groups. The subjects of the study were students of class X SMA Negeri 3 Pamekasan in the 2024-2025 Academic Year. The sample was selected using the cluster random sampling technique. The experimental class was taught using the role playing method while the control class used the conventional method in the form of lectures. Each control and experimental class had 36 students. The instrument used in this study was a descriptive test with 15 questions to measure learning outcomes and 10 questions to measure students' critical reasoning abilities. The data obtained were processed statistically using the SPSS statistic 21.0 application for windows in the Paired T test. The results of the study for the learning outcome variable obtained data values ​​of 0.000 (sig <0.05), Gain values ​​of 44.18 and N Gain of 0.7, including the high category. For the critical reasoning ability variable, a value of 0.000 (sig <0.05), Gain values ​​of 49.17 and N Gain of 0.7, included in the high category. The conclusion of this study is that the role playing method is effective in improving learning outcomes and critical reasoning abilities of class XI students of SMA Negeri 3 Pamekasan in describing the subject of chemistry on the material of molecular shapes.